2021
DOI: 10.5005/jp-journals-10006-1892
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Ability of Neutrophil–Lymphocyte Ratio in Pregnancy as a Predictor of Preeclampsia

Abstract: Aim and objective: Preeclampsia is part of the hypertension spectrum that occurs during the pregnancy period, especially when the gestational age is 20 weeks or more. Preeclampsia has a broad impact not only on pregnant women but also on the fetus they contain. It is said that in preeclampsia, there is an increase in inflammatory stimulation and an abnormal immune response so that routine blood values increase. Neutrophil-lymphocyte ratio (NLR) values reported in several studies have risen notably in the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…In 2019, Indonesia encountered considerable challenges in providing maternal healthcare, as reflected by its maternal mortality rate of 305 per 100,000 live births [3]. PE or eclampsia, hemorrhage, and infection, respectively, comprised 28%, 24%, and 11% of the direct obstetric causes of maternal death in the country [4,5]. Notably, 7-10% of pregnancies in Indonesia resulted in PE, highlighting the critical need for focused treatments and enhanced facilities for maternal healthcare [4].…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Indonesia encountered considerable challenges in providing maternal healthcare, as reflected by its maternal mortality rate of 305 per 100,000 live births [3]. PE or eclampsia, hemorrhage, and infection, respectively, comprised 28%, 24%, and 11% of the direct obstetric causes of maternal death in the country [4,5]. Notably, 7-10% of pregnancies in Indonesia resulted in PE, highlighting the critical need for focused treatments and enhanced facilities for maternal healthcare [4].…”
Section: Short Communicationmentioning
confidence: 99%
“…Notably, 7-10% of pregnancies in Indonesia resulted in PE, highlighting the critical need for focused treatments and enhanced facilities for maternal healthcare [4]. diverse strategy is needed to address these obstetric causes of maternal death but given the limited resources in most Indonesian healthcare facilities, optimizing existing resources becomes crucial [3][4][5].…”
Section: Short Communicationmentioning
confidence: 99%
“…It is derived from the full blood count values as the ratio of absolute neutrophil count to absolute lymphocyte count. This parameter is increasingly being utilized as an index of systemic inflammation in a plethora of clinical conditions such as sickle cell disease, [13] preeclampsia, [14] Diabetes mellitus, [15] cancers, [16] and in anaemia [17] among pregnant women. Clinical research confirmed the sensitivity of NLR in the diagnosis and stratification of systemic infections, sepsis, and bacteraemia as well as its robust predictive and prognostic values.…”
Section: Introductionmentioning
confidence: 99%
“…11 PE is the leading cause of fetomaternal morbidity and mortality. 12 Neonatal risks include intra-uterine growth restriction and low birth weight, perinatal death, and premature iatrogenic due to placental dysfunction and hypoxia. 13 Normal pregnancy occurs because there is a semi-allograph reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Changes occur in inflammatory cells in the blood, subsets of T lymphocytes, acute protein reactive, plasma inflammatory cytokine factors, complement activity, and coagulation systems that can later cause PE. 10,12 Neutrophil/lymphocyte ratio (NLR) is one of the inflammatory markers and is being widely studied today. The combination of two essential mechanisms in PE pathogenesis, the abnormal immune and inflammatory responses is the basis for evaluating the value of NLR as a prognostic modality to determine the severity of PE.…”
Section: Introductionmentioning
confidence: 99%